Analytical study of an iron deficiency anemia during pregnancy at tertiary care center - Dhameliya, Priya; Patel, Hemali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Anemia is a serious global public health problem affecting both developing and developed countries in reproductive age group. India contributes to about 80% of the maternal deaths due to anemia in south Asia. The objective was to analyse maternal and fetal outcome in anemic pregnant patients as compared to non anemic pregnant patients. Methods: This analytical study of 100 patients (50 anemic and 50 control groups) was conducted in department of obstetrics and gynecology, at tertiary care hospital, Surat from September 2022 to June 2023. Results: 56% were booked against 86% in the control group.44% were unbooked against 14% in the control group.66% in cases and 76% in controls were in majority age group of 21-29 years. 68% of the anemic women were multigravida as 50% in the control group.66% of the cases and 34% of the controls belongs to low socioeconomic class. Out of 50 cases of anemia 28% mild, 32% moderate and 40% severe degree. 32% anemic patients were managed with oral iron, 20% with parenteral iron therapy and 48% with blood transfusion. In cases, preeclampsia in 14 patients, preterm in 13 patients, PPH in 4 patients, while in control group 5 patients had preeclampsia, 6 patients had preterm labour and 2 patients had PPH. 1% maternal mortality in cases and zero in control groups. Conclusions: Antenatal management with correcting prenatal anemic status with dietary advises, prophylactic iron therapy, planned pregnancy with ensuring maternal iron sufficiency during gestation is most effective method.